Majorizacija vektorjev v RnaN - Prešeren, Ana Julija (Matrika, 2021)
The article presents vector majorization, its geometric interpretation and application in economy. It also presents the connection between vector majorization and doubly stochastic matrices. Three statements, equivalent to vector majorization, are formulated and proven in the last chapter.
Keywords: doubly stochastic matrices; dvojno stohastične matrike; majorizacija vektorjev; vector majorization